STABILITY OF THE RECONSTRUCTION DISCONTINUOUS STURM-LIOUVILLE PROBLEM - Ercan, Ahu; Panakhov, Etibar (Ankara Univ, Fac Sci, 2019)
In this work, we study stability of the inverse spectral problem for the Sturm-Liouville operator -D-2 + q with discontinuity boundary conditions inside a.nite closed interval. We use the method which is given by Ryabushko for regular Sturm-Liouville operator in [22] to obtain stability results. These results give a bound for the difference between the spectral functions of associated problems. In addition, we give asymptotic representation of the eigen-values and a formula for the representation of the norming constants by two spectra.
Keywords: Discontinuity; stability; spectral function; Sturm-Liouville